REKONSTRUKSI TEKS DAN ANALISIS FILOLOGIS NASKAH PAGAR TAWAR SITAHAN RASUN (NO.INV.1226/07.135): KOLEKSI MUSEUM NEGERI SUMATERA UTARA - Intan P. Siallagan; Warisman Sinaga; Ramlan Damanik (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2025)
Ancient manuscripts are cultural heritage assets that record past civilizations, knowledge systems, and beliefs of earlier societies. In Indonesia, several ethnic groups still preserve traditional manuscripts written in various indigenous scripts such as Bugis, Balinese, Javanese, Sundanese, Lampung, and Batak scripts. Batak manuscripts are known to contain traditional knowledge, including medicinal formulas, mystical practices, calendrical calculations, and prophecies. This study focuses on identifying the manuscript Pagar Tawar Sitahan Rasun (Inventory No. 1226/07.135), a collection housed at the North Sumatra Provincial Museum. The research applies a philological approach using a qualitative descriptive method to identify the manuscript’s physical and textual characteristics. The findings reveal eighteen essential elements of manuscript identity, including: (1) title, (2) inventory number, (3) storage location, (4) origin, (5) physical condition, (6) dimensions, (7) thickness, (8) number of lines per page, (9) script and writing type, (10) writing technique, (11) writing material, (12) text format, (13) estimated age, (14) language, (15) author (if known), (16) historical background, (17) social function, and (18) content summary. These findings contribute to the initial effort in preserving Batak manuscripts and provide a foundation for further studies on the cultural values contained within them